Telomere/telomerase dynamics within the human immune system: Effect of chronic infection and stress - Effros, Rita B. (Experimental gerontology, 2011)
Aging of the immune system is a major factor responsible for the increased severity of infections, reduced responses to vaccines, and higher cancer incidence in the elderly. A major category of stressors that contribute to the alterations within the T lymphocyte compartment is the family of herpes viruses. These viruses, usually acquired early in life, persist for many decades and drive certain T cells to the end stage of replicative senescence, which is characterized by a variety of phenotypic and functional changes, including altered cytokine profile, resistance to apoptosis, and shortened telomeres. Indeed, high proportions of senescent CD8 (cytotoxic) T lymphocytess are associated with latent cytomegalovirus (CMV) infection in the elderly, and are part of a cluster of immune biomarkers that are associated with early mortality. Similar cells accumulate at younger ages in persons chronically infected with HIV-1. In addition to persistent viral infection, psychological stress as well as oxidative stress can also contribute to the generation of senescent dysfunctional T lymphocytes. Strategies such as cell culture manipulation of replicative senescence, as well as lifestyle and stress reduction techniques are discussed in terms of possible approaches to enhance immune function in older persons. This review highlights the importance of using humans in studies on immunosenescence and telomere/telomerase dynamics, since model organisms employed in other facets of aging research are not subject to the particular factors that cause the striking age-related reconfiguration of the human immune system. ► Cellular aging of T lymphocytes is driven by latent viral infections. ► Oxidized lipids can accelerate this process. ► Psychological stress also accelerates T cell aging, via cortisol. ► Telomerase-based therapy may retard T cell aging.